Intersecting social and environmental determinants of multidrug-resistant urinary tract infections in East Africa beyond antibiotic use - Keenan, Katherine; Papathomas, Michail; Mshana, Stephen E.; Asiimwe, Benon; Kiiru, John; Lynch, AndyG.; Kesby, Mike; Neema, Stella; Mwanga, Joseph R.; Mushi, Martha F.; Jing, Wei; Green, Dominique L.; et al. (Nature Communications, 2024)
The global health crisis of antibacterial resistance (ABR) poses a particular threat in low-resource settings like East Africa. Interventions for ABR typically target antibiotic use, overlooking the wider set of factors which drive vulnerability and behaviours. In this cross-sectional study, we investigated the joint contribution of behavioural, environmental, socioeconomic, and demo graphic factors associated with higher risk of multi-drug resistant urinary tract infections (MDR UTIs) in Kenya, Tanzania, and Uganda. We sampled out patients with UTI symptoms in healthcare facilities and linked their micro biology data with patient, household and community level data. Using bivariate statistics and Bayesian profile regression on a sample of 1610 individuals, was how that individuals with higher risk of MDRUTIs were more likely to have compound and interrelated social and environmental disadvantages: they were on average older, with lower education, had more chronic illness, lived in resource-deprived households, more likely to have contact with animals, and human or animal waste. This suggests that interventions to tackle ABR need to take account of intersectional socio-environmental disadvantage as a priority.
Keywords: Global health crisis; Antibacterial resistance; Social and environmental determinants; Multidrug-resistant; Urinary tract infections; Antibiotic use; East Africa